Estudo das alterações vasculares na síndrome cardiorrenal: análise dos níveis de expressão dos receptores purinérgicos - Silva, Isabella Cardoso (2021)
Cardiorenal syndrome (CRS) characterizes by disorders of the heart and kidneys, in which acute or chronic dysfunction in one organ can induce acute or chronic dysfunction in the other. When acute renal failure leads to acute cardiac dysfunction, this syndrome is classified as SCR type 3 (SCR3). The vascular system is also affected by SCR but studies on possible vascular changes resulting from SCR distant from the site of renal ischemia, such as in the aorta, are scarce. Purinergic signaling, mediated by purines (ATP, ADP, adenosine) significantly impacts the vascular system, regulating vascular tone and inflammation, among other processes. The present study aimed to analyze the levels of gene expression of purinergic receptors P2Y1, P2Y2, P2Y6 and the pro-inflammatory cytokines IL-1β, IL-6, TNF-α, and fibrinogen α chain (FGA) in aortas from mice submitted to SCR3. C57BL/6 mice were submitted to the model of renal failure due to unilateral ischemia of the left renal pedicle for 60 minutes, followed by reperfusion for 8 and 15 days. Total RNA from thoracic aortas of Sham animals (control), IR 8 and IR 15 was extracted to analyze the expression levels of genes of interest by RT-qPCR. After 15 days of reperfusion, serum urea levels showed a significant increase, around 34% compared to the control group. Besides, the right kidney weight/tibia length ratio showed an increase of 17% in the IR15 group compared to the Sham group, validating the successful induction of the experimental model. The gene expression of the P2Y1 receptor decreased significantly, about 82 % at 8 and 15 days of reperfusion. The mRNA levels of the P2Y2 and P2Y6 receptors and the cytokines IL-1β, IL-6 and TNF-α were not altered between the experimental groups. However, the expression of FGA showed an important increase, approximately 690 times, in the aorta of IR15 mice compared to the Sham group. These findings contribute to a better understanding of the impact of SCR3 on blood vessels distant from renal ischemia, although further studies are needed. Also, considering the important role of purinergic receptors for vascular function, these results may in the future point to new diagnostic and therapeutic directions to be considered in patients with kidney disease.